Hasora mavis Evans, 1934 syn. n. is confirmed to be the female of H. leucospila leucospila (Mabille, 1891) (Hesperiidae, Coeliadinae) by DNA barcoding - Xue, Guoxi; Ikari, Etsuo; Inayoshi, Yutaka; Li, Meng (Zootaxa, 2019)
Based upon the comparison of the 649 bp COI gene sequences, Hasora mavis Evans, 1934 is proved to be the female of a sexually dimorphic species, H. leucospila leucospila (Mabille, 1891), and thus treated as a junior subjective synonym of the latter.